Pengaruh Kemandirian Belajar Siswa SMA Terhadap Kemampuan Komunikasi Matematik - Reka Nurhasanah; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
The study aims to determine the effect of learning independence of high school students on mathematical communication skills. The method used in this study was a correlational method with a quantitative approach. The population in this study was one of the high school students in West Bandung Regency and the sample was 32 students of the X Language class. The material used is a flat side space building material that has been taught in class VIII. The instrument in this study was a test of mathematical reasoning skills as many as 7 items of description questions and then the non-test instruments were in the form of a learning independence scale as many as 28 positive and negative revelations. The stage that was carried out in this study was filling in the test questions for mathematical communication skills then filling in the learning independence questionnaire. The results of this study conclude that student learning independence has a positive effect on mathematical communication skills of 57.7% and 42.3% influenced by other factors outside the independence of student learning